2000
DOI: 10.1507/endocrj.47.supplmarch_s17
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of 20K Human Growth Hormone in Normal Adults and Patients with Various Endocrine Disorders

Abstract: Abstract.The 20K hGH isoform is produced by alternative splicing of GH mRNA, and comprises approximately 10% of all GH in the pituitary.The physiological role of 20K hGH remains to be determined partly because of the lack of a simple and specific assay. We have established sensitive enzyme-linked immunoadsorbent assays (ELISAs) specific to 20K and 22K hGH. The serum levels of 20K hGH after overnight fasting was 118 ± 178 pg/mL (N = 282) in normal women, significantly higher than in normal men (64± 170 pg/mL, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Females usually have higher secretion rates, higher interpeak levels and more erratic secretion patterns of this isoform than males [ 34 ]. The 20 K-GH isoform has been reported to be higher in females than males, although the ratio of 20- to 22 K-GH usually does not differ between sexes [ 35 , 36 ]. 22 K-GH secretion patterns also change with age.…”
Section: Gh Isoform Secretion In Healthy and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Females usually have higher secretion rates, higher interpeak levels and more erratic secretion patterns of this isoform than males [ 34 ]. The 20 K-GH isoform has been reported to be higher in females than males, although the ratio of 20- to 22 K-GH usually does not differ between sexes [ 35 , 36 ]. 22 K-GH secretion patterns also change with age.…”
Section: Gh Isoform Secretion In Healthy and Diseasementioning
confidence: 99%
“…Some studies reported no influence of age, pubertal stage and sex on the 20 K/22 K-GH ratio in normal and GH deficient children and adults. There was also no change in 24-h GH secretion pattern after arginine and hypoglycemia stimulation tests [ 17 , 35 , 36 ]. Another group studied normal children after a different stimulation test (GHRH).…”
Section: Gh Isoform Secretion In Healthy and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Its smaller size is due to elimination of the first 45 nucleotides of the third exon of the mRNA and of the amino acids that correspond to positions 32-46 of the hormone, producing a protein with 176 amino acid residues (4). This isoform comprises approximately 10% of all the GH produced in the hypophysis and although it has not been shown to be the etiological agent of any known disease, it is known that its levels are significantly higher in patients with active acromegaly and in those with anorexia nervosa (5).…”
Section: Hgh20kmentioning
confidence: 99%